Financial development and productive inefficiency: a robust conditional directional distance function approach - Mallick, Sushanta; Matousek, Roman; Tzeremes, Nickolaos G. (Elsevier, 2016)
This paper examines whether the level of financial development helps lower countries’ inefficiency using time-dependent robust conditional directional distance functions in a sample of 91 countries over 1970–2011. The overall results reveal that the effect of financial development on countries’ productive inefficiency is highly nonlinear, and depends on countries’ income levels, suggesting that higher levels of financial development are enhancing more countries’ catching-up ability rather than their technological change.